miR-1290 contributes to oncogenesis and angiogenesis via targeting of THBS1, DKK3 and, SCAI - Mohammad Hasan Soheilifar; Majid Pornour; Massoud Saidijam; Rezvan Najafi; Farid Azizi Jalilian; Hoda Keshmiri Neghab; Razieh Amini (BioImpacts, 2022)
Introduction: Colorectal cancer (CRC) is the third most common cancer in the world with high mortality, hence, understanding the molecular mechanisms involved in the tumor progression are important for CRC diagnosis and treatment. MicroRNAs (miRNAs) are key gene expression regulators that can function as tumor suppressors or oncogenes in tumor cells, and modulate angiogenesis as a critical process in tumor metastasis. MiR-1290 has been demonstrated as an onco-miRNA in various types of cancer, however, the role of miR-1290 in CRC is not fully understood. This study aimed to investigate the oncogenic and angiogenic potential of miR-1290 in CRC. Methods: Lenti-miR-1290 was transduced into HCT116, SW480, and human umbilical vein endothelial cells (HUVECs). By bioinformatics analysis, we identified thrombospondin 1 (THBS1) as a novel predicted target for miR-1290. Quantitative real-time PCR, western blotting, and luciferase reporter assay were used to demonstrate suppression of miR-1290 target genes including THBS1, Dickkopf Wnt signaling pathway inhibitor 3 (DKK3), and suppressor of cancer cell invasion (SCAI) in HCT116 and HUVECs. Cell cycle analysis, proliferation, migration and, tube formation were determined by flow cytometry, MTT, wound healing, and tube formation assays, respectively. Results: MiR-1290 significantly decreased the expression of THBS1, DKK3, and SCAI. We demonstrated that miR-1290 enhanced proliferation, migration, and angiogenesis partially through suppression of THBS1, DKK3, and SCAI in CRC. Conclusion: These results suggest a novel function of miR-1290 which may contribute to tumorigenesis and angiogenesis in CRC.